PENGELOLAAN KEGIATAN BINA KELUARGA BALITA (BKB) SECARA HOLISTIK DAN INTEGRATIF - Farihah, Farihah; s, Masitowarni (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT Efforts 0f developing of human resources is a long-term process that should begin in early childhood.  According to the Presidential Regulation. 60 of 2013 that the Early Childhood children since the fetus   until the age of 6 years, which are grouped into: the fetus in the womb to be born; birth until the age of 28 days; aged 1 to 24 months, and ages 2 to 6 years. Family planning  program  pioneered since 1984 based on head SKB BKKBN and Minister of State for Women's Role (MEN FIU) No. 11 Kep / Men UPW/IX/84. 170/hk.010/E3/84. Family planning  program aims to enhance the knowledge and skills of parents in fostering the growth and development of Toddlers through physical stimulation, intelligence, emotional and social. Therefore  Family planning program should be implemented in an integrated, relevant and sustainable system. Early Holistic - Integrative Childhood Development are early childhood development efforts undertaken to meet the essential needs of children  with diverse and interrelated simultaneously, systematic, and integrated..Kata Kunci : Kegiatan BKB, holistik dan integratif.